2011
DOI: 10.1039/c0em00410c
|View full text |Cite
|
Sign up to set email alerts
|

Application of a battery of biomarkers in mussel digestive gland to assess long-term effects of the Prestige oil spill in Galicia and Bay of Biscay: Tissue-level biomarkers and histopathology

Abstract: In order to assess the biological effects of the Prestige oil spill (POS), mussels, Mytilus galloprovincialis, were collected in 22 localities along the North coast of the Iberian Peninsula over 3 years (April 2003-April 2006). Different tissue-level biomarkers including cell type composition (volume density of basophilic cells, Vv(BAS)) in digestive gland epithelium, structural changes of digestive alveoli (mean luminal radius to mean epithelial thickness, MLR/MET) and histopathological alterations (prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 86 publications
(185 reference statements)
11
70
2
7
Order By: Relevance
“…In both male and female samples with the TBBPA treatment, the hepatopancreas displayed conspicuous haemocytic infiltration and severe lesions of tubules. Infiltration of haemocytes in response to exposure to organic pollutants, such as PAHs and a mixture of diesel oil, has been reported in marine mussels (Auffert, 1988;Cappello et al, 2013a,b) and was interpreted as a repair process following tissue damage (Garmendia et al, 2011). Moore (1985) assumed that autolytic process of the epithelia of hepatopancreas tubule was a consequence of full lysosomal destabilization, which was confirmed by Auffert (1988) who found the incidence of lysosomes was inversely correlated to the extent of tubule lesions.…”
Section: Tbbpa Induced Damages and Apoptosis In Mussel Hepatopancreassupporting
confidence: 57%
“…In both male and female samples with the TBBPA treatment, the hepatopancreas displayed conspicuous haemocytic infiltration and severe lesions of tubules. Infiltration of haemocytes in response to exposure to organic pollutants, such as PAHs and a mixture of diesel oil, has been reported in marine mussels (Auffert, 1988;Cappello et al, 2013a,b) and was interpreted as a repair process following tissue damage (Garmendia et al, 2011). Moore (1985) assumed that autolytic process of the epithelia of hepatopancreas tubule was a consequence of full lysosomal destabilization, which was confirmed by Auffert (1988) who found the incidence of lysosomes was inversely correlated to the extent of tubule lesions.…”
Section: Tbbpa Induced Damages and Apoptosis In Mussel Hepatopancreassupporting
confidence: 57%
“…Under normal physiological conditions the digestive cells outnumber basophilic cells, but under different stress situations, including exposure to pollutants, the relative occurrence of basophilic cells is apparently augmented (Rasmussen et al, 1985;Lowe and Clarke, 1989;, 1998Zorita et al, 2006;Garmendia et al, 2011b). Changes in cell type composition in the digestive gland epithelium constitute a common response in molluscs that may lead to disturbances in food digestion and xenobiotic metabolism and accumulation Marigómez et al, 1998).…”
Section: Cell Type Composition In Digestive Gland Epitheliummentioning
confidence: 99%
“…Changes in the normal phasic activity may be attributed to environmental factors, such as food availability or saline and thermal stress (Winstead, 1995) as well as exposure to pollutants. Particularly, it has been widely demonstrated that molluscs exposed to pollutants exhibit a net mass loss in the digestive gland epithelium that gives rise to abnormal epithelial thinning and finally atrophy (Lowe et al, 1981;Couch, 1984;Lowe and Clarke, 1989;Vega et al, 1989;Marigómez et al, 1993;Garmendia et al, 2011b). Atrophy and epithelial thinning constitute a non-specific fast inducible and slowly or not recoverable response to stressful environmental conditions that can be measured after semi-quantitative scoring (Kim et al, 2006) or after quantitative morphological analysis in terms of MPTW (mean proportion of tubule width; Robinson, 1983); or in terms of mean epithelial thickness (MET) and the relative parameters MLR/MET and MET/MDR (Lowe et al, 1981;Vega et al, 1989;Marigómez et al, 1993;Garmendia et al, 2011b), where MLR is the mean luminal radius and MDR the mean diverticular radius.…”
Section: Digestive Tubule Epithelial Atrophy and Thinningmentioning
confidence: 99%
See 1 more Smart Citation
“…population, community or ecosystem (Cajaraville et al, 2000). Biomarkers have been applied in several species of molluscs, and especially in mussels, in both monitoring and experimental studies to establish timelines of exposure to and effects of xenobiotics and other anthropogenic perturbations (Garmendia et al, 2011;Viarengo et al, 2007;Zorita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%